WHAT’S SO SPECIAL ABOUT NISA HOMES? A CASE STUDY OF COMMUNITYBASED SHELTERS IN CANADA - Al-Nasser, Nour (Global Health: Annual Review, 2019)
While domestic violence occurs in all communities, and across all race and class lines, this study examines the barriers Muslim women face when accessing the Mainstream Canadian shelter system. It also presents a case study of Nisa homes, a community-based shelter for Muslim women, highlighting how it facilitates access and impacts women’s lives and wellbeing. This study employed qualitative tools, and is based on key informant interviews and focus group discussion with Nisa Homes staff and residents. The study identifies gaps in the Canadian shelter system, and underscores how barriers could be overcome by exploring innovative ways in which Nisa